2017
DOI: 10.1016/j.ramd.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity and exercise on male reproductive potential: a new assessment questionnaire

Abstract: Male athletes in general are subjected to the same causes of infertility as the general population, but sports practice itself may be possibly an additional infertility factor or, at least an aggravating factor for a previously existing fertility condition; on the contrary, being physically active has been hypothesized to favor hormonal and seminological processes and could be beneficial for fertility. In this relationship, the different inherent parameters of physical activity-exercise (training volume, inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 73 publications
(88 reference statements)
2
20
0
Order By: Relevance
“…Our analyses showed that DM resulted in a remarkable reduction in serum testosterone level and amplified the apoptosis ratio in the SDM animals. However, other studies have reported that training of animal models decreases the number of cells from spermatogenic lineage and is able to significantly reduce the enzymes and antioxidant agents (Manna et al, 2004;Vaamonde, Garcia-Manso, & Hackney, 2017). Accordingly, the animals in DM + EX and DM + INS + EX groups exhibited higher Leydig cells distribution/mm 2 , an improved TDI and SPI, lower apoptotic Leydig and germ cells and higher serum testosterone versus the SDM animals.…”
Section: However This Situation Was Reversed In Dm + Ins and Dm + Inmentioning
confidence: 82%
See 1 more Smart Citation
“…Our analyses showed that DM resulted in a remarkable reduction in serum testosterone level and amplified the apoptosis ratio in the SDM animals. However, other studies have reported that training of animal models decreases the number of cells from spermatogenic lineage and is able to significantly reduce the enzymes and antioxidant agents (Manna et al, 2004;Vaamonde, Garcia-Manso, & Hackney, 2017). Accordingly, the animals in DM + EX and DM + INS + EX groups exhibited higher Leydig cells distribution/mm 2 , an improved TDI and SPI, lower apoptotic Leydig and germ cells and higher serum testosterone versus the SDM animals.…”
Section: However This Situation Was Reversed In Dm + Ins and Dm + Inmentioning
confidence: 82%
“…In animal models, Torma and co-workers have reported that low inborn exercise capacity promotes the antioxidant system, and via this mechanism, it potentially up-regulates the spermatogenesis in rats (Torma et al, 2014). However, other studies have reported that training of animal models decreases the number of cells from spermatogenic lineage and is able to significantly reduce the enzymes and antioxidant agents (Manna et al, 2004;Vaamonde, Garcia-Manso, & Hackney, 2017). Therefore, considering limited contradictory data and to investigate the effect of moderate-intensity exercise training and insulin (both insole and simultaneous forms) on DM-induced oxidative stress, the tissue TAC, SOD and GPX levels were assessed.…”
Section: However This Situation Was Reversed In Dm + Ins and Dm + Inmentioning
confidence: 99%
“…More specifically, oxidative stress markers, antioxidant‐related enzymes, age‐related damage and DNA mutations have been reported to be reduced in the testicular tissue of animal models by endurance training (Chigurupati et al, ; Joseph et al, ; Zhao et al, ). In addition, seminal ROS level, the intensity of oxidative stress in testis and the rate of DNA fragmentation in spermatozoa were found to be diminished in physically active men when compared with higher level athletes (Tartibian & Maleki, , ; Vaamonde, Garcia‐Manso, & Hackney, ). Also, the effects of exercise on the antioxidant capacity of tissues, body fluids and blood serum have been well documented in many reports (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability of aerobic training to recover the SOD activity can indirectly lead to restoration of spermatogenesis. Besides, the influence of physical exercise on the testicular tissue depends on training intensity, volume and frequency (for review see Vaamonde et al, ). Additionally, both CPF and physical activity–exercise alter sex hormone levels in the body through affecting hypophyseal—gonadal and/or—thyroid axis and thus interfere with steroidogenesis, spermatogenesis and spermiation (Debnath & Mandal, ; Mandal & Das, ; Vaamonde et al, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is still no consensus on how physical activity might alter hypotalamo-pituitary-testicular axis. Some data suggest that endurance training might affect testosterone levels, usually in a negative way (decrease) and at the same time FSH levels are higher and mentioned changes imply compensatory hypogonadism as a result (Vaamonde, Garcia-Manso, & Hackney, 2017). According to research, heavy training lasting for several weeks leads to a decrease in the free testosterone/cortisol and free testosterone/SHBG ratio (Urhausen, Kullmer, & Kindermann, 1987;Vervoorn, et al, 1991).…”
Section: Discussionmentioning
confidence: 99%